O pensamento de Max Horkheimer nos anos 1930: filosofia e resistência - Ferreira, Thiago Pacheco (2013)
This dissertation discusses the thought of Max Horkheimer during the 1930s. The aim is to show the theoretical development of the philosopher during that period, explaining how the interdisciplinary materialism he proposed so he took the helm of the Institute for Social Research (ISP), in 1931, becomes the transdisciplinary materialism expressed on the essay Traditional theory and critical theory, from 1937. By conducting this study, we present how was the genesis of critical theory, the theoretical reference for thinkers placed under the label of the Frankfurt School . We point out that the 1937 article, considered the manifest of critical theory, actually results in an enhancement of the dialectical materialism interpretation that Horkheimer performs throughout the decade (away from the deterministic bias that supporters of proletarian revolution gave to Karl Marx thought). We show how Horkheimer s theoretical development in this period is based on attempts to resist the social, economical and political shifting conjuncture of the time, seeking for conditions to overcome the capitalist production model and establish an emancipated and rationally organized society in favor of the community (and not particular interests). Thus, in the early 1930s, when the revolution still seemed possible (through a transformation of the material basis conducted by the proletarian class), Horkheimer proposes a kind of closer to Marx materialism, with economy at the center of the other sciences arrangement. However, the advance of nazist totalitarianism and paralysis of the worker s movement, in addition to his exile in the United States (from 1934), slowly meant that the philosopher had to review the possible ways of resistance at that new conjuncture. This led him to propose a new theoretical model that incorporated psychoanalysis and removed the central role of the economy. This transdisciplinary arrangement sought to break the barriers of specialized sciences, using their concepts beyond each particular discipline planning. As such model Horkheimer gave the name of critical theory